Réponses

2013-11-01T17:12:13+01:00
Bonjour

a= (x + 1)(2x + 3) + 4(x + 1)
a = (x+1)(2x+3)  +4
a = (x+1)(2x+3+4)
 = (x+1)(2x+7)

b= (x + 1){au carré} - 25
b = (x+1)² -25
b = (x+1+5)(x+1-5)
b = (x+6)(x-4)

c= (x - 2){au carré} + 5(x - 2)

c= (x-2)² +5 (x-2)
c =(x-2)(x-2)+5
c =(x-2)(x-2+5)
c =(x-2)(x+3)

a= (x + 1)(2x + 3) + 4(x + 1)
a = (x+1)(2x+3) +4
a = (x+1)(2x+3+4)
= (x+1)(2x+7)

b= (x + 1){au carré} - 25
b = (x+1)² -25
b = (x+1+5)(x+1-5)
b = (x+6)(x-4)

c= (x - 2){au carré} + 5(x - 2)
c= (x-2)² +5 (x-2)
c =(x-2)(x-2)+5
c =(x-2)(x-2+5)
c =(x-2)(x+3)